PENINGKATAN KUALITAS AIR BAKU DENGAN PROSES BIOFILTER TERCELUP MENGGUNAKAN MEDIA STRUKTUR SARANG TAWON - Said, Nusa Idaman; Herlambang, Arie (Jurnal Air Indonesia, 2014)
Contamination of rivers has reached an alarming level, especially in the rivers passing through major cities, agricultural areas and industrial areas. Among the contaminants that often appear dominant and very disturbing is the organic substance. The existence of high organic matter within the river water is often expressed in permanganate number that has passed the quality standard. River that contain high organic matter usually the water smell and the color is black, besides it can also cause disturbances in the water treatment process, which is an increasing use of coagulants, chlorine, activated carbon, and the emergence of substances that are not desired, and the quality of treatment results are unsatisfactory. Many ways to reduce the organic matter in river water, one of them is by using the biofilter honeycomb structure. The target of the reduction of organic substances is that the river water could be used as a raw drinking water quality standards or meet the category B, Regulation of Jakarta Governor Number 582, 1995. Raw water used for this study were taken from Krukut River which is the raw water for Regional Water Company PALYJA, Production Installation III Cilandak, South Jakarta and Cengkareng Drain river water, which is currently used as a source of raw water for PAM Taman Kota, West Jakarta using a biofilter reactor aerobic system, the capacity of 50 - 200 m3, Capasity of Blowers 300 l /min, Residence Time 6 hours up to 1 hour. Test results on the residence time of 1 hour, parameters pH, TSS, turbidity, organic substances, detergents, manganese, ammonia, nitrite, nitrate, can meet the standard, except for iron which still exceeds the standard. To improve the removal efficiency of organic matter and iron, at the beginning of processing before entering into the drinking water treatment unit need to be added powder active carbon and an oxidizing agent with a sufficient dose. Keywords: Organic substances, biofilter, aerobic, honeycomb plastic media.